Pediocin PA-1 production by Pediococcus pentosaceus ET34 using non-detoxified hemicellulose hydrolysate obtained from hydrothermal pretreatment of sugarcane bagasse - Kuniyoshi, Taís Mayumi; Mendonça, Carlos Miguel Nóbrega; Vieira, Viviane Borges; Robl, Diogo; de Melo Franco, Bernadette Dora Gombossy; Todorov, Svetoslav Dimitrov; Tomé, Elisabetta; O'Connor, Paula Mary; Converti, Attilio; Araújo, Welington Luiz; Vasconcellos, Lívia Paula Silva Palmeiras; Varani, Alessandro de Mello [UNESP]; et al. (Elsevier, 2021)
Listeria monocytogenes is one of the foodborne pathogens of most concern for food safety. To limit its presence in foods, bacteriocins have been proposed as natural bio-preservatives. Herein, a bacteriocin was produced on hemicellulose hydrolysate of sugarcane bagasse by Pediococcus pentosaceous ET34, whose genome sequencing revealed an operon with 100% similarity to that of pediocin PA-1. ET34 grown on hydrolysate-containing medium led to an increase in the expression of PA-1 genes and a non-optimized purification step sequence resulted in a yield of 0.8 mg·L-1 of pure pediocin (purity > 95%). Culture conditions were optimized according to a central composite design using temperature and hydrolysate % as independent variables and validated in 3-L Erlenmeyers. Finally, a process for scaled-up implementation by sugar-ethanol industry was proposed, considering green chemistry and biorefinery concepts. This work stands up as an approach addressing a future proper sugarcane bagasse valorisation for pediocin production.
Keywords: Bacteriocin; Hemicellulose hydrolysate; Pediococcus pentosaceus; Sugarcane bagasse